Transient activation of mTOR following forced treadmill exercise in rats. Issue 9 (21st May 2013) - Elfving, Betina; Christensen, Tina; Ratner, Cecilia; Wienecke, Jacob; Klein, Anders B.
ABSTRACT The beneficial effect of exercise on hippocampal plasticity is possibly mediated by increased angiogenesis and neurogenesis. In angiogenesis, insulin‐like growth factor‐1 (IGF‐1), vascular endothelial growth factor (VEGF), and hypoxia‐inducible factor 1, alpha subunit (HIF1α) are important factors, while the induction of neurogenesis requires signaling through the VEGF receptor, Flk‐1 (VEGFR‐2). VEGF expression is believed to be regulated by two distinct mTOR (mammalian target of Rapamycin)‐containing multiprotein complexes mTORC1 and mTORC2, respectively. This study was initiated to investigate the effect of exercise on the expression of VEGF, cognate receptors, HIF1α, mTORC1, and mTORC2 in hippocampus and frontal cortex. To this end, we measured messenger RNA (mRNA) levels in rat brain using quantitative real‐time polymerase chain reaction (real‐time qPCR) after forced treadmill exercise for 1 day, 2 weeks, and 8 weeks. Rats were euthanized either immediately (0 h) or 24 h after last exercise session. Here, we show that exercise affected mRNA levels of VEGF, VEGFR2, and the coreceptor neuropilin 2 (NRP2) when the rats were euthanized immediately, whereas at 24 h only the expression of mTOR was regulated after a single bout of exercise. In conclusion, the effect of treadmill exercise on the VEGF system is acute rather than chronic and there is a transient activation of mTOR. More studies are needed to understand whether this could be beneficial in the treatment of neuropsychiatric disorders. Synapse 67:620–625, 2013. © 2013 Wiley Periodicals, Inc.